A guinada da igreja progressista em Sergipe : o bispado de Dom José Vicente Távora (1958-1970) - Santana, Glêyse Santos (2011)
This dissertation presents results of a study whose main objective was to identify and understand the social actions taken by the bishop Don José Vicente Silveira Távora in Sergipe (1958-1970). Such actions were here related to the senses and provisions established in the Brazilian Catholic field since 1930 to 1970 and to the discussion about the social issue that drove the Social Doctrine of the Church in Brazil. We also seek to highlight the following aspects: emergence, strategies, practices, discourses and symbolic goods offered by this bishop. Thus, the analysis of social actions of Dom Távora in Sergipe requires, above all, understanding the senses of that religious field, as well as the positions of the agent within this social sphere in the 1950s and 1960s, a period under the sign of the genesis of the catholic left and of its transformative ambitions. It s supposed that the social actions implemented by Dom Távora in Sergipe are directly associated with the defense of a Church model, which is manifested by the reform faction of the Brazilian clergy to which he was linked. Moreover, it s noted that the pictures attributed to him were the result of a construction career in defense of a direct action of the Church regarding the social issue, as well as its proximity to the intellectual and political field in Brazil.